2018
DOI: 10.1530/ec-17-0373
|View full text |Cite
|
Sign up to set email alerts
|

EDC IMPACT: Molecular effects of developmental FM 550 exposure in Wistar rat placenta and fetal forebrain

Abstract: Firemaster 550 (FM 550) is a flame retardant (FR) mixture that has become one of the most commonly used FRs in foam-based furniture and baby products. Human exposure to this commercial mixture, composed of brominated and organophosphate components, is widespread. We have repeatedly shown that developmental exposure can lead to sex-specific behavioral effects in rats. Accruing evidence of endocrine disruption and potential neurotoxicity has raised concerns regarding the neurodevelopmental effects of FM 550 expo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 93 publications
(129 reference statements)
2
18
0
Order By: Relevance
“…Evidence pertaining to cognitive-related effects of exposure to FM550 are more abundant. For example, available evidence suggests that exposure to FM550 disrupts endocrine system function [64], interferes with placental endocrine, inflammatory, and neurotransmitter signaling pathways [70], and can produce behavioral effects in model organisms [64,71,72]. Because FM550 as a mixture has been associated with cognitive-related effects, as have specific compounds of the mixture [63], the associations we observed with ip-PPP may be confounded by other components of FM550 (e.g., brominated components such as 2-ethylhexyl-2,3,4,5 tetrabromobenzoate and bis (2ethylhexyl) tetrabromophthalate) [63].…”
Section: Discussionmentioning
confidence: 99%
“…Evidence pertaining to cognitive-related effects of exposure to FM550 are more abundant. For example, available evidence suggests that exposure to FM550 disrupts endocrine system function [64], interferes with placental endocrine, inflammatory, and neurotransmitter signaling pathways [70], and can produce behavioral effects in model organisms [64,71,72]. Because FM550 as a mixture has been associated with cognitive-related effects, as have specific compounds of the mixture [63], the associations we observed with ip-PPP may be confounded by other components of FM550 (e.g., brominated components such as 2-ethylhexyl-2,3,4,5 tetrabromobenzoate and bis (2ethylhexyl) tetrabromophthalate) [63].…”
Section: Discussionmentioning
confidence: 99%
“…FM 550 contains a mixture of organophosphates: (1) triphenyl phosphate (TPHP; previously abbreviated TPP); and (2) a mixture of isopropylated triphenylphosphate isomers (ITPs); as well as two brominated compounds (3) 2-Ethylhexyl-2,3,4,5-tetrabromobenzoate (TBB); and (4) bis(2-Ethylhexyl)-2,3,4,5-tetrabromophthalate (TBPH). Work by us and others have identified this mixture to be developmentally neurotoxic, endocrine disrupting, and obesogenic [5][6][7][8][9][10][11][12][13]. Human exposure is nearly ubiquitous with both gestational and lactational transfer as significant exposure routes in addition to direct exposure via household dust, which is inadvertently ingested or inhaled [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…2020 ). Recent studies in rats exposed in utero to FM 550 have demonstrated that forebrain serotonin (5-HT) turnover was reduced, with evidence of endocrine disruption, inflammation, and altered neurotransmitter production found in the placentas ( Rock et al. 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Further, OPEs accumulate in rat placental tissue, in some cases to a higher degree in male-associated placentas than female (Phillips et al 2016;Baldwin et al 2017) and can induce functional changes, including altered neurotransmitter production (Rock et al 2020). Recent studies in rats exposed in utero to FM 550 have demonstrated that forebrain serotonin (5-HT) turnover was reduced, with evidence of endocrine disruption, inflammation, and altered neurotransmitter production found in the placentas (Rock et al 2018). In addition, serotonergic projections were shown to be significantly longer in the fetal forebrains of exposed males (Rock et al 2020).…”
Section: Mammalian Studiesmentioning
confidence: 99%